Faktor yang Berpengaruh Terhadap Pemakaian Metode Kontrasepsi Jangka Panjang pada Wanita Usia Subur di Jawa Timur (Data SDKI 2017) - Risyad Rosyadi (Universitas Airlangga, 2024)
Background: Long-Acting and Permanent Contraceptive Methods (LAPCM) is an effective and efficient method of contraception, but women of reproductive age prefer to use short term contraceptive methods. Objective: Analyze the factors that influence women of childbearing age in using long-term contraceptive methods in East Java in 2017 Methods: This type of research is non-reactive (unobtrusive) research, namely research for secondary data. The secondary data used is the 2017 IDHS. Results: The results of this study indicated the variables that affected the use of long-acting and permanent contraceptive methods of women of reproductive age was age (p=0.000), education level (p=0.000), number of alive children (p=0.000), sources of family planning services (p=0.000). Conclusion: Long-Acting and Permanent Contraceptive Methods (LPACM) most commonly used by women of childbearing age in East Java in 2017 were intrauterine devices of 38.4% then women’s surgery methods 32.3% and implants 29.3%. Factors influencing the use of Long-Acting and Permanent Contraceptive Methods in East Java Province in 2017, namely age, level of education, number of children born alive and sources of family planning services.